Cardioepigenetics in action: aerobic exercise-induced modulation of miRNAs, lncRNAs, and chromatin remodeling in cardiovascular disease - Shoudu Yuan; Qi Ye; Ran Qin (Frontiers in Cardiovascular Medicine)
Cardiovascular diseases (CVDs) remain a leading cause of morbidity and mortality worldwide, despite advances in prevention and therapy. Emerging evidence highlights the central role of epigenetic modifications and non-coding RNAs including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in the regulation of gene expression networks underlying cardiovascular homeostasis and disease. Concurrently, physical exercise has been recognized not only as a preventive and therapeutic strategy for CVDs but also as a potent modulator of epigenetic landscapes. This review explores the mechanistic links between aerobic exercise and epigenetic modulation, focusing on how structured physical activity influences the expression and function of miRNAs and lncRNAs, as well as chromatin remodeling processes in cardiovascular tissues. We provide a comprehensive overview of aerobic exercise-responsive non-coding RNAs implicated in vascular inflammation, endothelial function, cardiac remodeling, myocardial infarction, and atherosclerosis. Additionally, we discuss aerobic exercise-induced changes in DNA methylation and histone modification patterns that contribute to transcriptional reprogramming and long-term cardiovascular benefits. Finally, the review evaluates the translational potential of targeting aerobic exercise-regulated epigenetic factors for early diagnosis, risk stratification, and personalized therapies in CVD management. Understanding the molecular underpinnings of cardioepigenetic responses to exercise opens promising avenues for precision cardiovascular medicine and integrative therapeutic strategies.